2010
DOI: 10.1111/j.1365-2656.2009.01617.x
|View full text |Cite
|
Sign up to set email alerts
|

Paternally derived immune priming for offspring in the red flour beetle, Tribolium castaneum

Abstract: Summary1. Parasitized females in mammals, fish and birds can enhance the immune defence of their offspring by transferring specific antibodies for the embryo. Likewise, social insect mothers transfer immunity despite the fact that invertebrates lack antibodies. 2. Female trans-generational immune priming is consistent with parental investment theory, because mothers invest more into rearing their offspring than fathers. However, when immune priming is not directly linked to parental care, as is often the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
254
10
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 196 publications
(278 citation statements)
references
References 35 publications
(45 reference statements)
6
254
10
2
Order By: Relevance
“…4,8 However, the maternal transfer of bacteria or bacterial fragments does not explain the paternal immune priming of offspring in the red flour beetle T. castaneum, suggesting other mechanisms can be involved in this phenomenon. 11,28 In contrast, we observed the highest levels of immunity-related gene expression in G. mellonella eggs from individuals that had fed as larvae on pathogenic S. entomophila. This discrepancy can be explained by the different effects of injected soluble microbial elicitors and orallyadministered bacterial pathogens on immunity-related transcriptional reprogramming, as shown in T. castaneum.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…4,8 However, the maternal transfer of bacteria or bacterial fragments does not explain the paternal immune priming of offspring in the red flour beetle T. castaneum, suggesting other mechanisms can be involved in this phenomenon. 11,28 In contrast, we observed the highest levels of immunity-related gene expression in G. mellonella eggs from individuals that had fed as larvae on pathogenic S. entomophila. This discrepancy can be explained by the different effects of injected soluble microbial elicitors and orallyadministered bacterial pathogens on immunity-related transcriptional reprogramming, as shown in T. castaneum.…”
Section: Discussionmentioning
confidence: 55%
“…Maternal effects have been well documented in the context of trans-generational priming, and are thought to play a central role e.g., in the induction of offspring immunocompetence, but significant paternal effects have only been observed in a few studies. 11 Despite the increasing evidence for trans-generational immune priming in insects, the mechanism underlying the transfer of information from the parental generation to the offspring is unknown. The direct transfer of immune-related factors (e.g., lysozymes or antimicrobial peptides) in the cytoplasm of the egg has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Our analyses showed that while the results obtained from TER studies are largely consistent with our theoretical predictions, the signal is much less clear for TEI studies. We believe that an integrative view of the transgenerational immune memory requires both approaches [17,18,21,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been shown that parents of some invertebrates (mostly insects) may also transfer some specific immune factors to their offspring (Freitak et al 2009 and references therein). A novel study also challenges the long-held idea that fathers do not transmit immune information to their offspring: in the red flour beetle (Tribolium castaneum) offspring sired by males exposed to heat-killed bacteria were more resistant to a pathogen infection than offspring from non-exposed males (Roth et al 2010). Seminal substances, genomic imprinting and/or micro RNAs in the sperm could explain these findings (Roth et al 2010).…”
Section: Pathogensmentioning
confidence: 92%